ANALYSIS OF 1058 LUMBAR PROLAPSED INTERVERTEBRAL DISC CASES IN TWO TERTIARY CARE HOSPITALS OF PAKISTAN - Junaid, Muhammad; Rashid, Mamoon Ur; Afsheen, Afeera; Bukhari, Syed Sarmad; Kulsoom, Anisa (Journal of Ayub Medical College Abbottabad, 2016)
Background: Characteristics of Prolapsed Intervertebral Disc (PID) in two tertiary care hospitals of Pakistan. The objective of this was to study the demographic characteristics of lumbar PID by age, gender, clinical presentation, levels of spinal column involvement, treatment options and post-operative complications for lumber disc prolapse. Methods: One thousand and fifty eight cases (708 males, 350 females) of prolapsed intervertebral disc over six years between January 2009 and December 2014 were studied for location of prolapsed disks, gender, age, clinical presentation, treatment options and complications of surgery. Results: Of the determined locations L5/S1 was the commonest (34.6%), followed by L4/L5 (33.4%). 24.2%of the patients had prolapsed disks at 2 levels (L3/L4, L4/L5 andL4/L5, L5/S1). Prolapsed disc was commonest in the 31-49 year age group. Male were mostly affected with male to female ratio of 2.02%. Most common surgery performed was discectomy with fenestration (60.64% of total surgeries performed) and most common postoperative complication being mechanical backache (4.8%). Conclusion: Prolapsed intervertebral disc is common in the lower lumbar region at the level of L4/L5 and L5/S1. The outcome of the patients who underwent surgery is very good with 92.19% of patients, being free of postoperative complications. Keywords: Backache, lumbar disc prolapse, discectomy, sciatica